COVID‐19 and liver dysfunction: A systematic review and meta‐analysis of retrospective studies. Issue 10 (27th July 2020) - Youssef, Mohanad; H Hussein, Mohammad; Attia, Abdallah S; M Elshazli, Rami; Omar, Mahmoud; Zora, Ghassan; S Farhoud, Ashraf; Elnahla, Ahmad; Shihabi, Areej; Toraih, Eman A; S Fawzy, Manal; Kandil, Emad
Abstract: Recently, Coronavirus Disease 2019 (COVID‐19) pandemic is the most significant global health crisis. In this study, we conducted a meta‐analysis to find the association between liver injuries and the severity of COVID‐19 disease. Online databases, including PubMed, Web of Science, Scopus, and Science direct, were searched to detect relevant publications up to 16 April 2020. Depending on the heterogeneity between studies, a fixed‐ or random‐effects model was applied to pool data. Publication bias Egger's test was also performed. Meta‐analysis of 20 retrospective studies (3428 patients), identified that patients with a severe manifestation of COVID‐19 exhibited significantly higher levels of alanine aminotransferase, aspartate aminotransferase, and bilirubin values with prolonged prothrombin time. Furthermore, lower albumin level was associated with a severe presentation of COVID‐19. Liver dysfunction was associated with a severe outcome of COVID‐19 disease. Close monitoring of the occurrence of liver dysfunction is beneficial in early warning of unfavorable outcomes. Highlights: Liver dysfunction was associated with a severe outcome of COVID‐19 Sever cases of COVID‐19 patients have high serum levels of ALT, AST and bilirubin with prolonged prothrombin time. Low serum albumin is associated with a severe presentation of COVID‐19 Close monitoring of the occurrence of liver dysfunction is beneficial in early warning of unfavorable COVID‐19 outcomes.